Pengaruh Kecanduan Mobile Game Terhadap Gangguan Sosial Pada Era COVID-19 - Tony Wibowo; Nando Fransco (Universitas Internasional Batam, 2021)
Mobile games have become the alternative coping activity during Covid-19 Pandemic. This situation contributes greatly on student’s addiction level towards mobile games. This research was conducted to find out the impact of mobile games addiction towards depression, social anxiety, and loneliness of students in Batam specifically during pandemic of Covid-19. In this research, we employed quantitative method with the conceptual model from previous researchers. Furthermore, the technique of questionnaire distribution in this research had used Google Form and then were distributed to 402 respondents of students in Batam. The data was analysed with IBM SPSS Statistics 25. The outcome of this research showed that mobile games addiction has significantly caused depression, social anxiety, and loneliness. Therefore, from these findings, it is recommended to reduce or limit mobile games and try to find something positive.